2019
DOI: 10.15407/jnpae2019.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of natural radioactivity in soil samples of Badra oil field project using GIS program

Abstract: The study focuses on measuring the values of 238 U, 232 Th and 40 K natural radionuclides in soil samples in Badra oil field area (Iraq). Also, the radiological risk data were calculated for all samples in this study. The technique used in this study was gamma-ray spectrometry with NaI(Tl) detector. The averages of specific activity are: 24.7 Bq/kg for 238 U, 13.6 Bq/kg for 232 Th, and 538.9 Bq/kg for 40 K. Besides, the estimations of radiological effects like the radium equivalent (Ra eq ), the absorbed dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…for all samples were less than unity which is the Max. Value of the permissible safety limit recommended by the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR 2000) (18) .When comparing the results of the average specific activity of elements 238 U, 232 Th, and 40 k in the current study with the results recorded in different locations of Iraq (19)(20)(21)(22) , it is found that all results are larger than other previous studies. The increase or decrease of the recorded values is due to many factors such as the soil type, the geological nature of the area, the region selected (industrial or agricultural) or maybe exposure to other external factors.…”
Section: Discussionmentioning
confidence: 63%
“…for all samples were less than unity which is the Max. Value of the permissible safety limit recommended by the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR 2000) (18) .When comparing the results of the average specific activity of elements 238 U, 232 Th, and 40 k in the current study with the results recorded in different locations of Iraq (19)(20)(21)(22) , it is found that all results are larger than other previous studies. The increase or decrease of the recorded values is due to many factors such as the soil type, the geological nature of the area, the region selected (industrial or agricultural) or maybe exposure to other external factors.…”
Section: Discussionmentioning
confidence: 63%